2018
DOI: 10.1177/0883073818780105
|View full text |Cite
|
Sign up to set email alerts
|

Congenital Zika Syndrome and Infantile Spasms: Case Series Study

Abstract: Recently described, the congenital Zika syndrome caused by the Zika virus has many features of other congenital infections. This case series study reports 22 infants with congenital Zika syndrome in Brazil who developed infantile spasms during their first year of life. The median age of infantile spasms onset was 4.3 (±1.4) months and ranged from 1 to 7 months. Neurologic evaluation showed that all 22 children presented severe impairment of neuropsychomotor development. A total of 18 infants had an interictal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
35
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 12 publications
5
35
0
1
Order By: Relevance
“…At the end of 24 months, nearly three‐quarters of the monitored children had epileptic seizures, an incidence similar to that described in other studies of children with extensive lissencephaly . Other recent studies of microcephaly cases associated with congenital ZIKV infections have reported either similar or lower rates . Two factors may underlie the difference in rates.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…At the end of 24 months, nearly three‐quarters of the monitored children had epileptic seizures, an incidence similar to that described in other studies of children with extensive lissencephaly . Other recent studies of microcephaly cases associated with congenital ZIKV infections have reported either similar or lower rates . Two factors may underlie the difference in rates.…”
Section: Discussionsupporting
confidence: 81%
“…11,28 Other recent studies of microcephaly cases associated with congenital ZIKV infections have reported either similar 15 or lower rates. 12,13,15,16 Two factors may underlie the difference in rates. The first is the age range assessed.…”
Section: T a B L E 3 Clinical And Eegmentioning
confidence: 99%
See 1 more Smart Citation
“…Las pruebas de laboratorio para detectar el ZIKV en forma directa -detección del ácido ribonucleico (ARN) viral por reacción en cadena de la polimerasa con transcriptasa inversa (reverse transcription polymerase chain reaction; RT-PCR, por sus siglas en inglés)-e indirecta (IgM-ELISA y PRNT) realizados a la madre y al niño permiten la confirmación del SZC. [2][3][4][5][6][7][8][9][10][11][12][13][14][15] En el suero, el virus es detectable desde el comienzo de los síntomas, hasta el día 6 y, en la orina, a partir del día 5 hasta el día 15. La IgM es dosable a partir del día 4 y la inmunoglobulina G (IgG), a partir del día 7 del inicio de los síntomas, y ambos persistirían en el suero hasta 12 semanas.…”
Section: Discussionunclassified
“…8,9 Due to the nature and severity of injuries to the CNS, epilepsy is a frequent finding and may lead to clinical deterioration. [10][11][12] Most clinical descriptions of CZVS are based on infants at an early age. At this stage of life, epilepsy occurs in 58.3%-71.4%.…”
mentioning
confidence: 99%